Determining the Effectiveness of Noncontact Three‐Dimensional Surface Scanning for the Assessment of Open Injuries. Issue 2 (2nd October 2019) - Shamata, Awatif; Thompson, Tim
Abstract: Noncontact three‐dimensional (3D) surface scanning methods are used within forensic medicine to record traumas and other related findings. A structured light scanning technique is one of these methods and the most suitable for the forensic field. An assessment of the efficiency of different structured light scanners with forensic injuries is essential to validate this technique for wound documentation. The purpose of this study was to evaluate the capability of the HP structured light scanner Pro S3 for digitizing open injuries having complicated areas and depths. Fifteen simulated injuries on mannequins were scanned and assessed. Comparisons between 3D and direct wound measurements were made. The results showed that the technique was able to create detailed 3D results of the extensive injuries. Statistical significance tests revealed no difference between the two measurement methods. Because the scanner is applicable for routine work, it should be considered to confirm the same results on real cadavers and actual wounds.